Metacognitive learning strategies in argumentative writing skills - Erwin Oktoma; Zainal Rafli; Aceng Rahmat (University of Kuningan, 2020)
This study aims to determine the effect of metacognitive learning strategies on students' argumentative writing skills. This research was conducted on third semester students of the English education study program, Faculty of Teacher Training and Education, Universitas Kuningan. A quantitative approach was chosen with an experimental data collection technique tests as a used method, namely: (1) Test of argumentative writing skills. This study examines the effect of metacognitive learning strategies on students' argumentative writing skills. The learning strategies used are metacognitive learning strategies (experimental class) and control class concept map learning strategies. The findings indicate that metacognitive learning strategies are effective in teaching students' argumentative writing in English. Regarding the results of this study, the application of different learning strategies is needed in students' argumentative writing learning. Based on the results and conclusions above, it turns out that metacognitive learning strategies have a significant effect on students' argumentative writing skills in English. Thus, this research provides a beneficial implication in planning and developing learning strategies which will be used in improving students' argumentative writing skills in English, especially with regard to the application of appropriate learning strategies. The argumentative writing skills of students who were given metacognitive learning strategies were better than those who were given concept map learning strategies instead. In this case, the role of the lecturer is very important so that to improve students' argumentative writing skills, metacognitive strategies are more effectively applied in class